Penambahan Serbuk Kulit Jeruk Bali pada Pembuatan Selai Cempedak dengan Pemanis Stevia: The Addition of Pomelo Peel (Citrus maxima) Powder in Cempedak (Artocarpus champeden) Jam with Stevia Sweetener - Rachmat, Aisyah Indriani; Nurhalimah, Siti; Lestari, Tiara Amanda (Jurnal Ilmiah Pangan Halal, 2025)
Jam is a semi-solid food product from fruit, sugar, pectin, acid, and water. This study evaluates the effect of adding grapefruit (Citrus maxima) peel powder on the physical, chemical, and sensory characteristics of cempedak (Artocarpus integer) jam with stevia. The study design used a completely randomized design (CRD) with one factor: the concentration of grapefruit peel powder (0%, 0.5%, 1%, and 1.5%), with two replications each. The parameters observed included viscosity, water content, ash, pH, fiber content, total soluble solids, sensory quality tests (color, aroma, taste, texture), and hedonic evaluation. The results showed that adding grapefruit peel powder significantly affected viscosity, crude fiber content, and total soluble solids. Treatment A3 (1% grapefruit peel powder) was determined as the best treatment. Treatment A3 had a high crude fiber content of approximately 7.21%, viscosity of 16.71%, total soluble solids of 15.75%, a yellow-brown color, and good spreadability. This study demonstrates the potential of utilizing grapefruit peel as a source of natural pectin and stevia as a low-calorie sweetener to develop healthier and more functional jam products.